Effect of Drying Post-Harvest on the Nutritional Compounds of Edible Flowers - Jean Santos Machado; Ylenia Pieracci; Giulia Carmassi; Barbara Ruffoni; Andrea Copetta; Laura Pistelli (Horticulturae, 2023)
The post-harvest techniques are the most critical point to ensure the quality of edible flowers (EFs) and to keep the bioactive metabolites available for human nutrition. The different species of EFs also represent a problem in improving their consumption with safety. The present study focused on the description of the effects of the commonly used drying treatments in the phytonutritional composition of four species of EFs, Callianthe megapotamica, Callianthe striata, Nemesia strumosa and Salvia elegans. The bioactive metabolites and antioxidant activity were determined after freeze-drying (FD) and hot-air-drying (HA) treatments in comparison to fresh flowers. All EFs showed different mineral/trace compositions with potassium as the main element and 70–86% water loss. Both post-harvest treatments increased all the metabolites and antioxidant activity in each species. C. striata with FD treatment had the highest content of primary and secondary metabolites. N. strumosa has the highest ascorbic acid content with the HA treatment. All species had significant antioxidant activity, increasing with FD for C. striata while HA is more recommended for the other species. The post-harvest techniques are able to preserve and increase the bioactive metabolites and must be chosen according to each EF species.